117k views
3 votes
Solve the system by the elimination method.

2x + 3y - 10 = 0
4x - 3y - 2 = 0
When you eliminate y, what is the resulting equation?

-6x = 12

6x = 12

6x = -12

2 Answers

2 votes

Answer:

Equation 6x = 12.

Explanation:

Given : 2x + 3y - 10 = 0 and 4x - 3y - 2 = 0 .

To find : When you eliminate y, what is the resulting equation.

Solution : We have given

2x + 3y - 10 = 0 -------(equation 1)

4x - 3y - 2 = 0 --------- (equation 2)

On adding both the equations.

2x + 3y - 10 = 0 .

4x - 3y - 2 = 0 .

_____________

6x + 0 - 12 = 0.

6x - 12 = 0 .

On adding both sides by 12

6x = 12.

Therefore, Equation 6x = 12.

User Sudha Bisht
by
5.9k points
6 votes

Answer:

6x = 12

Explanation:

2x + 3y - 10 = 0

4x - 3y - 2 = 0

add the two equations

2x + 3y - 10 = 0

4x - 3y - 2 = 0

--------------------

6x -12 = 0

add 12 to each side

6x -12 +12 = 0+12

6x =12

divide by 6

6x/6 =12/6

x =2


User Kannan Goundan
by
5.2k points